Introducing Twitter as an assessed component of the undergraduate nursing curriculum: case study. (10th February 2016) - Jones, Ray; Kelsey, Janet; Nelmes, Pam; Chinn, Nick; Chinn, Teresa; Proctor‐Childs, Tracey
Abstract: Aims: To ask: (i) is it feasible to include Twitter as an assessed element of the first‐year nursing curriculum; (ii) how should it be introduced and assessed; and (iii) do students think it worthwhile and learn anything from its use? Background: Nursing students need to use social media professionally, avoiding pitfalls but using learning opportunities. Design: This case study (2014–2015) comprised: (i) pilot introduction of Digital Professionalism (including Twitter) with second‐ and third‐year students; (ii) introduction and assessment with a first cohort of 450 first‐year students. Based on feedback, methods were revised for; (iii) a second cohort of 97. Methods: Students received a face‐to‐face lecture, two webinars, used chat rooms and were asked to create course Twitter accounts and were assessed on their use. Results: Few second and third year students started optional Twitter use whereas nearly all first years used it. Most students (70·1% first, 88·0% second cohort) thought inclusion of Twitter was worthwhile. Changes from first to second cohort included better peer–peer support, more contextualization and more emphasis on nursing communities. More second cohort students learned from Twitter (44·4% vs. 70·8%) and used Twitter recently (43·3% vs. 81·6%). Students gained wider perspectives on nursing, better understanding of social media, 'being student nurses' and topics like health promotion. Students mostly followed not only online nursing communities but also patient organizations. Conclusion: Including Twitter as an assessed element for first‐year nursing students was feasible, students think it worthwhile and other nursing schools should consider introducing it in the broader context of Digital Professionalism.